USE OF DIODE LASER FOR GINGIVAL MELANIN DEPIGMENTATION - Maria Bolat; Dana Bosînceanu; Raluca Baciu; Ioana Mârţu; Norina Forna; Doriana Agop-Forna (Romanian Journal of Oral Rehabilitation, 2018)
Gingival melanin pigmentation is a physiologic condition which does not present any medical problem, but clinicians are often faced with a challenge of achieving gingival esthetics in such cases. The color of gingiva is determined by number and size of blood vessels, thickness of epithelium, keratinization degree, and melanin pigments present in epithelium. Melanocytes, located in basal and suprabasal layers of epithelium, are the cells that produce melanin pigments which play a main role for pigmentation of gingiva. In this case report, the use of 940 nm diode laser for depigmentation of gingiva is presented. A female patient applied with a chief complaint of “darkened gums” due to heavy smoking. In intraoral examination, diffuse melanin pigmentation was observed in both the maxilla and mandible. Under the local anesthesia, 940 nm diode laser was applied for depigmentation at 2 W power in continuous mode. The patient was recalled at 3 and 7 days after intervention to evaluate the healing and recurrence rate. The patients had no postoperative pain or edema, and complete healing was observed after one week . This study revealed that depigmentation with 940 nm diode laser is successful in terms of esthetics and patient comfort.